Process optimization for the development of quinoa based sugar free ice-cream - Vasundhara; Amrita Poonia (Indian Journal of Dairy Science, 2022)
Quinoa has high nutritional value and rich source of lipids, proteins, vitamins, fibre, minerals and magnificent balance of amino acids. The major objective of this study was to develop high protein and sugar free ice cream incorporated with malted quinoa flour. The standard method of ice cream preparation was followed with incorporation of 10, 15 and 20 per cent malted quinoa flour during homogenization. Addition of more than 20 per cent quinoa flour in ice-cream imparts increased raw flavour, hardness and viscosity. Based on organoleptic evaluation, ice cream prepared with 15 per cent malted quinoa flour was accepted as optimized with higher values of acceptance for colour, flavor, texture and overall acceptability. Â The physico- chemical composition of optimized ice cream observed were 10.50 ± 0.08 % fat, 4.21 ± 0.08 % protein, 14.01 ± 0.05 % carbohydrates, 37.92 ± 0.39 % total solids, 1.84 ± 0.25 % crude fibre, 16.91 ± 0.02(mg/ml) total phenolic content and 66.25 ± 2.53 (mg/ml) antioxidants. During storage period some of the sensory attributes, physico-chemical, bio-active compounds and microbiological count of the quinoa ice-cream and the control sample was analysed after every 5th day for 35 days. At the end of the storage period, anti-oxidant, over run, melting resistance and pH decreased but acidity increased slightly.